Pengaruh Kualitas Pelayanan Publik dan Komunikasi Publik terhadap Kepuasan Masyarakat Nagari Koto Tangah Kecamatan Tilatang Kamang - Amanta Zahra; Dasman Lanin (Lembaga Yasin AlSys, 2026)
The quality of public services and effective public communication are important factors in increasing community satisfaction and strengthening trust in government institutions. However, service delivery at the nagari government level still requires continuous evaluation to ensure its alignment with community needs and expectations. This study aims to analyze the effects of public service quality and public communication on community satisfaction in Nagari Koto Tangah, Tilatang Kamang Subdistrict. The study employed a quantitative approach using a survey method. Data were collected by distributing questionnaires to community members and analyzed using multiple linear regression, partial tests (t-tests), simultaneous tests (F-tests), and the coefficient of determination. The results showed that public service quality had a positive and significant effect on community satisfaction, with a t-value of 32.380 and p < 0.001. Public communication also had a positive and significant effect on community satisfaction, with a t-value of 30.697 and p < 0.001. Simultaneously, public service quality and public communication had a significant effect on community satisfaction, with an F-value of 563.899 and p < 0.001. The adjusted R-squared value of 0.753 indicates that the two variables explained 75.3% of the variation in community satisfaction, while the remaining 24.7% was influenced by other factors outside the research model. These findings confirm that improving service quality, supported by transparent, responsive, and effective public communication, is an important factor in increasing community satisfaction with nagari government services. Practically, the findings can serve as a basis for the Nagari Koto Tangah Government to continuously improve its service standards and public communication strategies.